Strategi Guru Geografi dalam Meningkatkan Motivasi Belajar Siswa pada Pembelajaran Geografi di SMA Negeri 1 Airmadidi Kabupaten Minahasa Utara - Lausan, Juvia Anjel; Karwur, Hermon Maurits; Rifani, Irfan; Nugroho, Cahyadi (Jurnal Social Science, 2024)
This research aims to analyze the strategies employed by geography teachers at SMA Negeri 1 Airmadidi to enhance students' intrinsic and extrinsic motivation. A qualitative methodology was utilized, incorporating literature review, observations, interviews, and documentation for data collection. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings reveal that students respond positively to the strategies implemented by teachers, such as paying attention to the teacher, engaging with the material presented, and demonstrating active participation in learning activities. These strategies contribute to positive student behaviors, including helping peers, effective time management, active engagement in the learning process, achieving good academic results, and striving for success. However, several factors hinder the efforts of teachers to enhance student motivation in geography learning. These factors include individual motives, lack of uniformity in teaching methods, limited media usage, inadequate environmental conditions, insufficient parental attention, and low motivation levels among students. To overcome these barriers, teachers can create a conducive learning environment, intensify interactions with students, employ enjoyable learning traps, and establish a supportive atmosphere for learning.